EVALUATION OF QUALITATIVE PHYTOCHEMICAL CONSTITUENTS AND IN VITRO ANTI-DIABETIC ACTIVITY OF CARDIOSPERMUM HALICACABUM L. - MERINA PAUL DAS; Y. YASMINE; P.VENNILA DEVI (International Journal of Pharma and Bio Sciences, 2015)
Diabetes mellitus is a chronic endocrine disorder that affects the metabolism of carbohydrates due to absolute or relative deficiency of insulin. In recent years, there is a sharp increase in the incidence and prevalence of diabetes mellitus which demands an effective and immediate approach to cure it. One of the anti-diabetic therapeutic approaches is to reduce the post prandial glucose level in blood by the inhibition of the intestinal digestive enzymes, such as alpha-amylase and alpha-glucosidase. The objective of the present work was to analyze the phytochemicals qualitatively and to evaluate the anti-diabetic activity of different polar and non-polar extract of Cardiospermum halicacabum L. in vitro conditions. Different concentrations of extracts were used for the evaluation of alpha-amylase and alpha-glucosidase inhibition activity. The assay results suggest that all the extract of C. halicacabum exhibit dose-dependent increase in inhibitory activity on α-amylase and α-glucosidase enzymes due to the presence of phytoconstituents. This infers that C. halicacabum can be used as a potent herbal drug for the treatment of diabetic patients.